RUSSIANIZATION POLICY OF TSARISM AND BULLYING IN GEORGIAN EDUCATIONAL SPACE ACCORDING TO THE GEORGIAN PRESS OF THE 80S AND 90S OF THE 19TH CENTURY GEORGIANS’ FIGHT FOR THE PROTECTION OF GEORGIAN LANGUAGE - Imeri Basiladze; Sophio Panchulidze (International Journal of Innovative Technologies in Social Science, 2019)
In 1801 after invading Georgia, Russia started to fight hard to break Georgian national consciousness, for this it was necessary to demolish the Georgian language. There are many noteworthy notes about the current situation in the magazines and newspapers of 80s and 90s of the 19th century which were published in Kutaisi. Here you will find information how the native language was prohibited, the study of Georgian children was restricted, and the schools were guided by Russians. "Mute Method" was introduced at schools. Russia tried to prove the unnecessity of the Georgian language. For example, if the number of Georgians in one of the educational institutions exceeded the number of other ethnicities, they tried not to find the learners who came from different parts of Georgia as Georgians in order to avoid the need for teaching Georgian language.At the same time, on the paper of the Georgian press you can find some speeches, protests. Some schools were closed. Georgians demanded the change of educational system. In general, all these served to protect the Georgian language and to strengthen its positions.Thus, in the 80s and 90s of the 19th century, the Georgian press leaders strictly criticized Russia's Tsarism educational policy because it did not meet the interests of the Georgian people. They thought that the content of the teaching should reflect the true nature of the people. It should be an active propagandist and conductor of national ideas.